Seasonal dynamics of the trophic structure of an assemblage of Coleoptera in the Colombian Amazon - NORIEGA-A., JORGE ARI; BOTERO, JUAN PABLO; VIOLA, MARCELO; FAGUA, GIOVANNY (Revista Colombiana de Entomología, 2007)
To understand the different patterns of seasonal variation in the trophic structure of coleopteran assemblages, a study was conducted in the Colombian Amazon, over three consecutive years in wet and dry seasons, in both tropical rain forest and floodplains. Transect sampling was carried out with pitfall, Corner, Winkler, and Malaise traps as well as manual capture. The material was identified to family level. A total of 3,691 individuals was captured, corresponding to 32 families. The families most abundant in numbers of individuals were Scolytidae (31.7%), Scarabaeidae (22.2%), and Staphylinidae (18.1%). The xilomycetophages (32.1%) were the dominant group, followed by the copro-necrophages (22.3%), predators (21.7%) and herbivores (11%). A comparison among years and habitats revealed differences in the abundance and composition of the families, as well as in the contribution of the trophic roles. The dry season shows a tendency to impoverishment. The marked spatial and temporal variation among seasons and years is associated with high diversity and would support the hypothesis that seasonality plays an important role in diluting interspecific competition for resources.